Pengaruh Faktor Internal dan, Eksternal terhadap Risiko Kredit pada Bank Perkreditan Rakyat (BPR) di Indonesia - I Made Sudana; Andi Siti Asiyah (Jurnal Manajemen dan Bisnis Indonesia, 2018)
This study aims to know the effect of internal factor (capitalization, profitability, inefficiency, size) and external factor (economic growth, inflation) on credit risk of micro bank in Indonesia. This research uses purposive sampling method. Dependent variable in this research is credit risk. The independent variables in this study are capitalization measured by capital adequacy ratio, profitability measured by return on asset, inefficiency measured by BOPO ratio, size, economic growth, and inflation. The results show that credit risk is significantly influenced by capitalization, profitability, inefficiency, size, economic growth, and inflation. Inefficiency and inflation variables have a positive effect on credit risk, while variable capitalization, profitability, size, and economic growth negatively affects credit risk. Keywords: capitalization, profitability, inefficiency, size, economic growth, inflation, credit risk, rural bank.